2021
DOI: 10.21203/rs.3.rs-215837/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Bread Enriched With Portulaca Oleracea on Metabolic Control Indices in Patients With Type 2 Diabetes: a Parallel Randomized Clinical Trial

Abstract: Background: Diabetes is the most common chronic disease worldwide. Some herbs are used to control diabetes. Portulaca Oleracea is a type of plant that has essential fatty acid-rich leaves. Objectives: This study aimed to evaluate the effect of bread enriched with Portulaca Oleracea on metabolic control indices in patients with type 2.Methods: This parallel randomized controlled clinical trial was conducted on 104 patients with type 2 diabetes. Participants received bulk bread containing 10% Portulaca powder fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
(52 reference statements)
0
11
0
Order By: Relevance
“…
Today, attention has been drawn to the consumption of functional foods (Asadzadeh et al, 2021). These functional foods are known as food products with beneficial physiological activity and more health properties for consumers (Delvarianzadeh et al, 2020;Maghazechi et al, 2021). Functional products include a wide range of food products, one of the most important of which is food products containing probiotic microorganisms called probiotic products (Frakolaki et al, 2020).
…”
mentioning
confidence: 99%
“…
Today, attention has been drawn to the consumption of functional foods (Asadzadeh et al, 2021). These functional foods are known as food products with beneficial physiological activity and more health properties for consumers (Delvarianzadeh et al, 2020;Maghazechi et al, 2021). Functional products include a wide range of food products, one of the most important of which is food products containing probiotic microorganisms called probiotic products (Frakolaki et al, 2020).
…”
mentioning
confidence: 99%
“…A 5-point hedonic scale (1 = very bad, 2 = bad, 3 = mediate, 4 = good, and 5 = very good) was used. From F I G U R E 1 Obtained pick for aflatoxin B1, aflatoxin B2, aflatoxin G1, and aflatoxin G2 by immunoaffinity column high-performance liquid chromatography each treatment, six pistachio nut samples were placed in special colorless plastic containers and offered to each assessor to evaluate four main sensory attributes: color, aroma, flavor, and overall acceptability (Delvarianzadeh et al, 2020).…”
Section: Sensory Attributesmentioning
confidence: 99%
“…[6] There are numerous reports in the available literature on various medicinal plants and how they are used on food products in various applicable forms, including essential oils, aqueous and alcoholic extracts, as well as the powdered dry matter of different plant parts. [7][8][9][10] In this regard, Hematian Sourki, et al [11] reported that the use of lemon verbena powder and essential oil increased the quality characteristics, antioxidant potential and shelf life of the cookies. Roy and Guha [12] reported that cupcakes containing betel leaf essential oils had better quality characteristics, sensory and textural properties than commercial cupcakes, and marketing reports showed that consumers were more motivated to buy this product than commercial samples.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] There are numerous reports in the available literature on various medicinal plants and how they are used on food products in various applicable forms, including essential oils, aqueous and alcoholic extracts, as well as the powdered dry matter of different plant parts. [ 7–10 ] In this regard, Hematian Sourki, et al. [ 11 ] reported that the use of lemon verbena powder and essential oil increased the quality characteristics, antioxidant potential and shelf life of the cookies.…”
Section: Introductionmentioning
confidence: 99%